Data Processing Algorithms while Executing Acoustic Non-Contact Search for Leakages in Top Block of LWPR-1000 Reactor - V. A. Boltenkov; A. V. Korolev; M. V. Maximov; O. V. Maslov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2009)
The paper presents an algorithm of signal processing against actual leakages simulated with the help of an experimental thermo-physical stand. The algorithm for evaluation of leakage coordinates has been developed in the paper and it is based on the signal processing  which are received by every four microphone transducers. Higher accurateness has been achieved while applying an area method of local coherence.